PERAN STRATEGI INOVASI DAN PENGUATAN MUTU PRODUK DALAM MENINGKATKAN KEPUASAN PELANGGAN PADA PRODUK KOMODITAS HASIL OLAHAN KAYU DAN TURUNANNYA DI KALIMANTAN TIMUR - Nona, Risna; Joko Prayitno; Nur Maulida Sari (DE FACTO : Journal Of International Multidisciplinary Science, 2025)
This study aims to examine the role of innovation strategies and product quality improvement on customer satisfaction in processed wood products and their derivatives in East Kalimantan. The research employed a survey method by distributing questionnaires to 278 respondents selected from a population of 1,616 consumers using simple random sampling based on the Slovin formula. The collected data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the WarpPLS software. The results indicate that innovation strategies and product quality have a positive and significant effect on customer satisfaction. This finding suggests that companies capable of implementing continuous innovation and maintaining high product quality are better able to meet customer needs and expectations. Therefore, improving product quality and innovation is essential in enhancing customer satisfaction and strengthening the competitiveness of processed wood products in the market.